Preparation for the development of literacy in children aged 4 to 5 - Panchana Comilla, Teresa de Jesús; Barreiro Moreira, Dunia Lucía (SATHIRI, 2025)
The general objective of this research was to analyze the level of development of readiness for reading and writing in children aged 4 to 5 years. This is a qualitative study with a concurrent, field, transversal and non-experimental explanatory design. The population considered is made up of 70 students and 22 teachers, while the intentional sample represents 50% of the total population. Techniques such as survey and observation were used in data collection, using instruments such as the questionnaire and observation guide. The diagnosis of academic performance in preparation made it possible to obtain valuable information about the children’s strengths and weaknesses in this area, in addition to evaluating their levels of linguistic competence and reading comprehension. This facilitated the implementation of more appropriate and personalized pedagogical strategies, designed to strengthen their skills, enhance their development and foster their self-confidence.